The Phenomenon of Divorce Due to Social Media (Study of Decisions at the Lubuk Pakam Religious Court in 2021-2022) - Usada, Widia; Akbar, Ali (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2024)
This research aims to explore the facts regarding the use of social media in the family as a trigger for divorce and analyse efforts to prevent divorce caused by social media. The focus of this research is the relevance between social media and divorce, where social media is often the trigger for ongoing disputes and arguments between married couples. Based on data, 60% of divorces in the Lubuk Pakam Religious Court in 2021-2022 were caused by the use of social media. The research method used is normative law with a qualitative approach, using primary data sources from decisions of the Lubuk Pakam Religious Court and in-depth interviews with judges and the head of the Religious Affairs Office. The results showed that the use of social media in the family must be regulated by certain norms to prevent disputes. Social media has been shown to be closely linked to divorce, being a major factor in triggering repeated disputes and arguments. Prevention efforts by the Religious Affairs Office and Religious Courts are expected to be an effective solution to reduce the divorce rate due to the use of social media.